Robotic vs. Laparoscopic Splenectomy in Management of Non-traumatic Splenic Pathologies: A Systematic Review and Meta-Analysis. Issue 1 (January 2022) - Bhattacharya, Pratik; Phelan, Liam; Fisher, Simon; Hajibandeh, Shahab; Hajibandeh, Shahin
We aimed to evaluate comparative outcomes of robotic and laparoscopic splenectomy in patients with non-traumatic splenic pathologies. A systematic search of electronic databases and bibliographic reference lists were conducted, and a combination of free text and controlled vocabulary search adapted to thesaurus headings, search operators and limits in electronic databases were applied. Intraoperative and post-operative complications, wound infection, haematoma, conversion to open procedure, return to theatre, volume of blood loss, procedure time and length of hospital stay were the evaluated outcome parameters. We identified 8 comparative studies reporting a total of 560 patients comparing outcomes of robotic ( n = 202) and laparoscopic ( n = 258) splenectomies. The robotic approach was associated with significantly lower volume of blood loss (MD: −82.53 mls, 95% CI −161.91 to −3.16, P = .04) than the laparoscopic approach. There was no significant difference in intraoperative complications (OR: 0.68, 95% CI .21-2.01, P = .51), post-operative complications (OR: .91, 95% CI .40-2.06, P = .82), wound infection (RD: -.01, 95% CI -.04-.03, P = .78), haematoma (OR: 0.40, 95% CI .04-4.03, P = .44), conversion to open (OR: 0.63; 95% CI, .24-1.70, P = .36), return to theatre (RD: −.04, 95% CI -.09-.02, P = .16), procedure time (MD: 3.63; 95% CI -16.99-24.25, P = .73) and length of hospital stay (MD: −.21; 95% CI -1.17 - .75, P = .67) between 2 groups. In conclusion, robotic and laparoscopic splenectomies seem to have comparable perioperative outcomes with similar rate of conversion to an open procedure, procedure time and length of hospital stay. The former may potentially reduce the volume of intraoperative blood loss. Future higher level research is required to evaluate the cost-effectiveness and clinical outcomes